Proline, a unique amino acid whose polymer, polyproline II helix, and its analogues are involved in many biological processes: a review - Théoneste Umumararungu; Noël Gahamanyi; Janvier Mukiza; Gratien Habarurema; Jonathan Katandula; Alexis Rugamba; Vedaste Kagisha (Amino Acids)
Abstract Proline is a unique amino acid in that its side-chain is cyclised to the backbone, thus giving proline an exceptional rigidity and a considerably restricted conformational space. Polyproline forms two well-characterized helical structures: a left-handed polyproline helix (PPII) and a right-handed polyproline helix (PPI). Usually, sequences made only of prolyl residues are in PPII conformation, but even sequences not rich in proline but which are rich in glycine, lysine, glutamate, or aspartate have also a tendency to form PPII helices. Currently, the only way to study unambiguously PPII structure in solution is to use spectroscopies based on optical activity such as circular dichroism, vibrational circular dichroism and Raman optical activity. The importance of the PPII structure is emphasized by its ubiquitous presence in different organisms from yeast to human beings where proline-rich motifs and their binding domains are believed to be involved in vital biological processes. Some of the domains that are bound by proline-rich motifs include SH3 domains, WW domains, GYF domains and UEV domains, etc. The PPII structure has been demonstrated to be essential to biological activities such as signal transduction, transcription, cell motility, and immune response.